Profitabilitas Sebagai Pemoderasi Pengaruh Pengungkapan Sustainability Reporting Pada Nilai Perusahaan Pemenang Indonesian Sustainability Reporting Awards - Budiana, Quita Amelia; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi, 2020)
This study aims to determine the effect of Sustainability Reporting on firm value and determine the ability of profitability in moderating the effect of Sustainability Reporting on firm value. This research was conducted on the winners of the Indonesian Sustainability Reporting Awards (ISRA) in 2015-2018. The number of samples taken as many as 13 companies using purposive sampling techniques. The data analysis technique used is Moderated Regression Analysis (MRA). Based on the results of the analysis found that Sustainability Reporting has a positive effect on firm value and profitability strengthens the effect of Sustainability Reporting on firm value. Keywords: Sustainability Reporting; Firm Value; Profitability.